Inteligencia emocional y trabajo en equipo: Un nuevo enfoque para liderar organizaciones - Salas Biondi, Luis Leonidas (2024)
Recent research has demonstrated the impact of emotional intelligence on organizational results. In addition, it has become a key requirement for successful management. Based on this, the objective of this research was to determine the extent to which emotional intelligence influences teamwork in an industrial company. For this purpose, a quantitative, descriptive, correlational, non-experimental and cross-sectional approach was used as the research method. The instrument used was a 32-question questionnaire that was administered to 110 employees of an industrial company in Lima. The instrument obtained a reliability level of 0.8574 according to Cronbach's Alpha and the results were statistically confirmed by Spearman's Rho, which shows a positive relationship of 0.613. In addition, it was statistically determined that 70.7% of the employees apply the techniques of emotional intelligence and that 77% have a positive attitude towards teamwork. Considering the result of this research on emotional intelligence and teamwork in an industrial company, it is concluded that there is a moderate positive relationship and that it has an impact on organizational management. Therefore, the present results will provide scientific and reliable bases to promote training in the use of emotional intelligence techniques in order to promote teamwork, improve productivity, obtain the maximum benefit from individual interaction and facilitate the development of collective talent.